2023
DOI: 10.1101/2023.10.24.23297458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complementary, Alternative, and Integrative Medicine Researchers’ Practices and Perceived Barriers Related to Open Science: An International, Cross-Sectional Survey

Jeremy Y. Ng,
Lucas J. Santoro,
Kelly D. Cobey
et al.

Abstract: Introduction and Objective: Open science (OS) aims to make the dissemination of knowledge and the research process transparent and accessible to everyone. With the increasing popularity of complementary, alternative, and integrative medicine (CAIM), our objective was to assess practices and perceived barriers towards OS among CAIM researchers. Methods: We conducted an anonymous online survey of researchers who published in journals listed in Scopus containing the words "complementary", "alternative", or "integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A survey study conducted on author usage of open science practices found that while many authors are familiar with the idea of open science, many lack knowledge on how to implement these practices [56]. In another survey on CAIM author attitudes about open science, funding was found to be a major barrier to applying open science practices in research [57]. Both of these findings can serve as starting points for investigating how journals can better facilitate the use of open science research practices.…”
Section: Plos Onementioning
confidence: 97%
“…A survey study conducted on author usage of open science practices found that while many authors are familiar with the idea of open science, many lack knowledge on how to implement these practices [56]. In another survey on CAIM author attitudes about open science, funding was found to be a major barrier to applying open science practices in research [57]. Both of these findings can serve as starting points for investigating how journals can better facilitate the use of open science research practices.…”
Section: Plos Onementioning
confidence: 97%
“…Clearance from the University Hospital Tübingen Research Ethics Board was obtained prior to starting this project (REB Number: 389/2023BO2). The study protocol was registered and made available on Open Science Framework (OSF) 43 prior to recruiting participants. The study materials and raw data were shared on OSF 44 .…”
Section: Transparency Statementmentioning
confidence: 99%
“…Approval was granted by the Research Ethics Board at the University Hospital Tübingen before beginning this project (REB Number: 389/2023BO2). Prior to recruiting participants, the study protocol was registered and made available on the Open Science Framework (OSF) [42].…”
Section: Transparency Statementmentioning
confidence: 99%